The association of current exclusive e-cigarette use and dual use of e-cigarettes and cigarettes with psychological distress among U.S. adults - Yingning Wang; Hai-Yen Sung; Shannon Lea Watkins; James Lightwood; Tingting Yao; Wendy Max (Preventive Medicine Reports, 2023)
This observational study examines the association of current e-cigarette use and dual use of e-cigarettes and cigarettes (dual use) with psychological distress among U.S. adults. We differentiate dual use based on the smoking frequency and compare the relationship between dual use and psychological distress to that of exclusive cigarette smoking with the same smoking frequency.Using data from the 2015–2018 National Health Interview Surveys, we analyzed adults aged 18+ (N = 55,780) who currently use e-cigarettes or/and cigarettes and have no history of using other tobacco products, and adults who never used any tobacco. Multinomial logistic regression models estimate the association of current e-cigarette use and dual use with psychological distress severity (no/mild, moderate, and severe).In the sample, 15.3% and 2.9% of adults experienced moderate and severe psychological distress. Compared to never tobacco users, current exclusive e-cigarette users and dual users who smoke daily had higher odds of moderate and severe psychological distress. Dual users who smoke nondaily had higher odds of moderate, but not severe psychological distress than never tobacco users. Compared to exclusive daily smokers, dual users with daily smoking had higher odds of moderate and severe psychological distress. Compared to exclusive nondaily smokers, dual users with nondaily smoking had higher odds of moderate but not severe psychological distress.Our findings suggest that exclusive e-cigarette use is associated with psychological distress severity. Dual use is associated with higher odds of psychological distress severity compared to never tobacco users and exclusive cigarette smoking, and this association differs by smoking frequency.